Protection of IFNAR (-/-) mice against bluetongue virus serotype 8, by heterologous (DNA/rMVA) and homologous (rMVA/rMVA) vaccination, expressing outer-capsid protein VP2. - Tamara Kusay Jabbar; Eva Calvo-Pinilla; Francisco Mateos; Simon Gubbins; Abdelghani Bin-Tarif; Katarzyna Bachanek-Bankowska; Oya Alpar; Javier Ortego; Haru-Hisa Takamatsu; Peter Paul Clement Mertens; Javier Castillo-Olivares (PLoS ONE)
The protective efficacy of recombinant vaccines expressing serotype 8 bluetongue virus (BTV-8) capsid proteins was tested in a mouse model. The recombinant vaccines comprised plasmid DNA or Modified Vaccinia Ankara viruses encoding BTV VP2, VP5 or VP7 proteins. These constructs were administered alone or in combination using either a homologous prime boost vaccination regime (rMVA/rMVA) or a heterologous vaccination regime (DNA/rMVA). The DNA/rMVA or rMVA/rMVA prime-boost were administered at a three week interval and all of the animals that received VP2 generated neutralising antibodies. The vaccinated and non-vaccinated-control mice were subsequently challenged with a lethal dose of BTV-8. Mice vaccinated with VP7 alone were not protected. However, mice vaccinated with DNA/rMVA or rMVA/rMVA expressing VP2, VP5 and VP7 or VP2 alone were all protected.